The Influence of Digital Marketing, Online Reviews, and Brand Image on Decision to Stay at Adhiwangsa Apartment, Surabaya (LACULTOUR: Journal of Language and Cultural Tourism, 2026)
This study examines the influence of digital marketing, online reviews, and brand image on consumers' decision to stay at Adhiwangsa Apartment, Surabaya. A quantitative explanatory design was employed using purposive sampling, resulting in data from 79 respondents who had booked or stayed at the property through digital platforms. Data were analyzed using multiple linear regression. The findings reveal that digital marketing does not have a significant direct effect on decision to stay, indicating that promotional activities alone are insufficient to influence consumers' choices for high-involvement accommodation services. In contrast, online reviews have a positive and significant effect, highlighting the dominant role of electronic word-of-mouth in reducing information uncertainty and strengthening consumer confidence. Brand image demonstrates a positive but statistically insignificant influence, suggesting that reputation alone cannot drive decision to stay without being supported by positive customer experiences and credible online information. The study extends the application of the Theory of Planned Behavior and Signaling Theory to the premium apartment context by demonstrating that digital credibility and social validation outweigh promotional communication in shaping consumer decisions. These findings provide practical implications for accommodation managers to prioritize digital reputation management, encourage authentic customer reviews, and deliver consistent service quality to enhance competitiveness in an increasingly digital hospitality environment.